Effects of times and storage conditions of Duddingtonia flagrans chlamydospores in sodium alginate pellets on its nematode predatory ability. Issue 7 (3rd July 2019) - Li, Qiong Yi; Wang, Feng; Yang, Xue Cai; Wan, Xue Mei; Zhao, Tian Yu; Chang, Fan Fan; Du, Jiang Long; Wang, Bo Bo; Jia, Xiao Ye; Zhou, Xue Yan; Ran, Qian Dong; Pan, Hong; et al.
ABSTRACT: This study aimed to determine the effects of Duddingtonia flagrans contained in sodium alginate pellets on trichostrongylide larvae under different storage conditions and durations. The in vitro predatory activity of D. flagrans in pellets against trichostrongylide larvae in sheep faeces were assessed at 0, 1, 3, 6, 9, and 12 months after the pellet was stored under four different conditions (i.e. −20, 4°C, outdoors, and indoors). These results revealed that the numbers of larvae in faeces of sheep treated with pellets containing chlamydospores (treatment groups) were significantly lower than those in the control groups (without chlamydospores) for all trial months under four storage conditions for different durations ( p < .05). The obtained reduction rates of the infective larvae (L3) in the four treatment groups ranged from 45.62% to 96.73% throughout the entire experiment. The overall mean L3 reduction percentages were 89.22% ± 3.74%, 88.97% ± 1.33%, 68.60% ± 14.31%, and 75.45% ± 13.18% for 4°C refrigeration, −20°C refrigeration, indoor, and outdoor conditions, respectively. The pellets stored under these storage conditions for a year were provided to sheep for ingestion ( in vivo test), and the results showed that the number of recovered larvae in sheep faeces at 24 h after ingestion were significantly lower than that before ingestion. For in vivo test, the L3 reduction percentage in the faeces was 90.99% (−20°C), 74.81% (outdoor), 83.53% (4°C), and 65.60% (indoor). Under the four storage conditions, D. flagrans spores contained in the pellets can maintain their survival ability to a varying degree in a year.